The problem of fraud in the banking industry: Are biometrics the answer?. (23rd January 2012) - DeVries, Peter D.
Fraud is a growing problem in the banking industry. New legislative requirements have highlighted biometric technology as a reliable secondary means of authentication. This study is a review of literature on biometrics with a focus on feasible alternatives and implementation issues in the banking industry. The literature indicates that techniques like retinal scanning show promise. However, standards are needed in the following areas: (1) allowable degree of invasiveness, (2) desired ease of use, (3) use of biometric data and (4) security of biometric data templates. It is difficult to quantify savings from implemented systems. Therefore, top management should be involved in adoption decisions.